RESEARCH OF NEUROTOXICITY OF ACRYLATES IN EXPERIMENT AND IN WORKERS OF ACRYLONITRILE PRODUCTION - M. M. Tarskikh (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In the experiment on the integral evaluation criteria we studied neurotoxidty of acrylates — acrylonitrile and acrylamide; moreover the neurotoxidty indices of acrylonitrile were more expressed than those ones of acrylamide. Under production conditions it is revealed that the chronic intoxication by acrylonitrile causes the development of the syndromes of the defeat of nervous system in people. Is established the dependence of gravity of defeat on the period of professional contact with the poison and its content in air of working zone, and also on the content of acrylonitrile, connected with hemoglobin of erythrocytes in this birth cohort.